Hermansky-Pudlak syndrome with a novel genetic variant in HPS1 and subsequent accelerated pulmonary fibrosis: significance for phenocopy diseases. Issue 11 (25th June 2018) - McElvaney, Oliver J; Huizing, Marjan; Gahl, William A; O'Donovan, Paul; Horan, Deirdre; Logan, P Mark; Reeves, Emer P; McElvaney, Noel G
Abstract : The Hermansky-Pudlak syndrome (HPS) is a collection of autosomal-recessive disorders characterised by tyrosinase-positive oculocutaneous albinism (OCA), bleeding diatheses and, in selected individuals, early-onset accelerated pulmonary fibrosis, neutropaenia and granulomatous colitis. We describe a young man who presented following a self-directed literature review prompted by severe bleeding complications following minor surgical and dental procedures in the context of OCA. HPS was clinically suspected, with subsequent genetic testing confirming biallelic mutations in the HPS1 gene. Of interest, this is the only described HPS type 1 patient with two different (compound heterozygote) splice site variants in HPS1 . In addition to detailing a novel genetic result and outlining the progressive clinical course of disease in this case, we discuss the management of HPS, the prognostic value of subtype analysis and the technical difficulties relating to transplantation in the case of HPS-associated advanced pulmonary fibrosis. This case also illustrates the concept of lung phenocopy relationships and the potential for elucidating the pathogenesis of more common pulmonary disorders by studying genetic diseases that result in similar phenotypes. Furthermore, it re-emphasises the importance of the patient voice, particularly with regard to complex diagnoses and rare diseases.